2009
DOI: 10.1186/1471-2229-9-152
|View full text |Cite
|
Sign up to set email alerts
|

Virus infection elevates transcriptional activity of miR164a promoter in plants

Abstract: BackgroundMicro RNAs (miRs) constitute a large group of endogenous small RNAs that have crucial roles in many important plant functions. Virus infection and transgenic expression of viral proteins alter accumulation and activity of miRs and so far, most of the published evidence involves post-transcriptional regulations.ResultsUsing transgenic plants expressing a reporter gene under the promoter region of a characterized miR (P-miR164a), we monitored the reporter gene expression in different tissues and during… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
64
0
4

Year Published

2010
2010
2015
2015

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 64 publications
(71 citation statements)
references
References 69 publications
(114 reference statements)
3
64
0
4
Order By: Relevance
“…To determine whether the EIN3-induced reduction of miR164 occurs by repressing miR164 transcription, we generated transgenic plants that harbor GUS driven by the miR164A promoter (pmiR164A:GUS) (Bazzini et al, 2009) in the Col-0, ein2-5, and ein3 eil1 backgrounds. We found that GUS activity significantly decreased in 5-d-old pmiR164A:GUS/Col-0 seedlings upon treatment with 100 mM ACC ( Figures 5G and 5I), indicating that ethylene negatively regulates miR164 transcription.…”
Section: Ein3 Represses Mir164mentioning
confidence: 99%
See 2 more Smart Citations
“…To determine whether the EIN3-induced reduction of miR164 occurs by repressing miR164 transcription, we generated transgenic plants that harbor GUS driven by the miR164A promoter (pmiR164A:GUS) (Bazzini et al, 2009) in the Col-0, ein2-5, and ein3 eil1 backgrounds. We found that GUS activity significantly decreased in 5-d-old pmiR164A:GUS/Col-0 seedlings upon treatment with 100 mM ACC ( Figures 5G and 5I), indicating that ethylene negatively regulates miR164 transcription.…”
Section: Ein3 Represses Mir164mentioning
confidence: 99%
“…The pmiR164A:GUS construct, a 2522-bp fragment upstream of the foldback structure of miR164A, was provided by Sebastian Asurmendi (Bazzini et al, 2009). pmiR164A:GUS construct was introduced into Agrobacterium tumefaciens C58 and transformed into Col-0, ein3 eil1, or ein2-5 plants by floral dip (Clough and Bent, 1998).…”
Section: Construction Of Plasmids and Generation Of Transgenic Plantsmentioning
confidence: 99%
See 1 more Smart Citation
“…For example miR1885 is induced in response to infection of Brassica rapa by Turnip mosaic virus and is known to target a TIR-NBS-LRR (TNL) disease-resistance gene [53]. miR164 is also induced upon viral infection and its induction is due to hormone-dependent specific transcriptional activation [54]. However, the effect of this differential regulation in the outcome of the interaction is not well established, as it may also result from the silencing suppression activity of the virus.…”
Section: Sncrnas and Viruses: New Frontiers Of Defensementioning
confidence: 99%
“…For mechanical wounding treatments, leaves were gently pressed with a pair of sterilized serrated forceps as described Delessert et al (2005) and collected at 1, 2 or 3 hrs after wounding. Hormone treatments were performed according to Bazzini et al (2009). Briefly, plants subjected to hormone treatment were grown in 1.5 inches individual pots and sprayed with 50 ml of 100 μM ABA, 100 μM IAA, 50 μM GA3 or water (mock-treated) and incubated for 6 hrs under dim light.…”
Section: Transformation Constructs and Plant Transformationmentioning
confidence: 99%